Performance Analysis and Optimisation During Machining of Al-ZrB2 Reinforcement-Based Metal Matrix Nanocomposites Using Coated and Uncoated Insert - Seema V. Yerigeri; Vaijanath V. Yerigeri (Journal of Engineering)
Lightweight and high-strength composites attract attention towards the different industrial applications. Reinforcement in base material makes composite operate at high working temperatures. The continuous pursuit of improving machining processes in the manufacturing industry has led to the development of these advanced materials and innovative tooling techniques. In this present research, focus is on the experimental study of the performance enhancement during machining operations on the fabricated different aluminium-based metal matrix nanocomposites (Al-MMNC) by employing temperature sensors and a dynamometer to monitor the material behaviours. The investigation involves a comparative analysis of cutting force (CF) and temperature at the tool tip to understand their respective effects on machining performance. Through comprehensive experimental trials conducted, the CF, material removal rate (MRR), temperature and surface roughness (Ra) values are quantified to determine the performance between both coated and uncoated inserts. Enhancement of these characteristics depends on factors like alloy grade, reinforcement type and its wt.%, speed and feed applied during machining. Main aim of the present work is to obtain the optimum combination of factors and their levels. Al 7075, Al6082 and Al 6063 are selected alloy levels, while zirconium diboride (ZrB2) reinforcement levels are set at 6, 9 and 12 wt.%. Speed levels are set at 112, 180 and 280 rpm, and feed rates are set at 0.15, 0.20 and 0.25 mm/rev. Al 7075 alloy with 12% ZrB2 reinforcement set at speed rate 280 rpm and feed rate at 0.20 mm/rev at constant depth of cut of 0.5 mm using uncoated insert gave the optimum values of response variables at the composite desirability of 0.69 from the Taguchi statistical analysis. The effects of CF, MMR, Ra and temperature on machining analysis of nanocomposites are provided in the article.